2002
DOI: 10.1016/s0360-8352(02)00055-4
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary algorithm for optimizing material flow in supply chains

Abstract: Supply chain management literature calls for coordination between the different members of the chain. Materials should be moved from one supplier to the next according to a just-in-time schedule. In this paper we develop an evolutionary algorithm (EA) for optimal synchronization of supply chains. In developing our algorithm, we use the economic delivery and scheduling model and analyze supply chains dealing with multiple-components. We test the performance of the proposed EA and show that it provides optimal, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 10 publications
0
27
0
2
Order By: Relevance
“…Vergara et al [57] developed a heuristic Evolutionary Algorithm (EA) for scheduling the part processes within the suppliers and setting the synchronized delivery cycle time for the supply chain. They compared the results with enumeration of all solutions and showed that the heuristic solution provides optimal or near-optimal solutions faster than enumeration methods as the problem size gets larger.…”
Section: Solution Methodologiesmentioning
confidence: 99%
“…Vergara et al [57] developed a heuristic Evolutionary Algorithm (EA) for scheduling the part processes within the suppliers and setting the synchronized delivery cycle time for the supply chain. They compared the results with enumeration of all solutions and showed that the heuristic solution provides optimal or near-optimal solutions faster than enumeration methods as the problem size gets larger.…”
Section: Solution Methodologiesmentioning
confidence: 99%
“…It is supposed to match customer demand that is, producing only enough to replenish what the customer has used or sold. Vergara et al (2002) have dealt the co ordination between different parts of simple supply chain. Materials should be moved from one supplier to other supplier as per the JIT.…”
Section: Supply Chain Systemmentioning
confidence: 99%
“…The genetic algorithms of simulation-based optimization models in the supply chain networks are supported through mathematical programming [101][102][103]. However, these studies mostly deal with strategic decisions, for instance combinatorial operation research problems such as multi-stage facility location, rather than tactical or operational ones.…”
Section: Integrated Simulation-based Optimization Modelsmentioning
confidence: 99%